Caracterização físico-química do mel do bioma pampa brasileiro e estudo do seu potencial antioxidante in vitro e in vivo em modelo de Drosophila melanogaster - Cruz, Litiele Cezar da (2014)
Honey is a complex mixture produced by honey bees from the nectar, which is used by its sweetening properties, as well as by its human health benefits. The aim of this study was to characterize, for the first time in literature, the Brazilian Pampa Biome honey in terms of quality parameters and determination of its antioxidant properties in vitro and in vivo. A total of 10 honey samples were tested for physicalchemical parameters, as moisture, free acidity, reducing sugars, hydroxymethylfurfural (HMF) levels, among others. The antioxidant activity (in vitro), as evaluated by total phenolics, flavonoid content, FRAP and DPPH-ABTS scavenging activity. Drosophila melanogaster (in vivo) were exposed to oxidative stress induced by Iron (Fe) and Paraquat (PQ) in different treatment protocols, in the presence or absence of honey. The survivorship and locomotor activity (negative geotaxis) were analyzed. Possible glycemic alterations on honey diet were also evaluated. The results of physicochemical analysis indicated that all honeys were in accordance with the standards established by the Brazilian law, in which follows international standards. All honey samples showed significant antioxidant activity in vitro. Flies treated with honey showed increased lifespan and were protected against oxidative stress induced by Fe and PQ in the different treatment protocols (48h and 7 days), in regards of mortality and locomotor deficits. Despite the high sugar content of honey, glucose content were unchanged in honey fed flies, when compared to flies fed on honey-equivalent amounts of sugars. This study demonstrates that Brazilian Pampa Biome honey has a high quality level, a significant antioxidant activity in vitro and a protective potential against oxidative stress (in vivo). It has been also demonstrated that Drosophila melanogaster could be a valid model for studies with honey, as well as the usage of this natural product as an alternative in the therapy of oxidative stress-associated diseases.